Odpowiedzi

2009-12-13T19:07:28+01:00
√80-√72/√80+√72 - √80+√72)/√80-√72
wspólny mianownik = ( √80+√72 )*(√80-√72 )
wówczas mamy:
[(√80-√72)*(√80-√72 ) -( √80+√72)*( √80+√72)] :[( √80+√72 )*(√80-√72 )]
=[ (√80 -√72)² - ( √80+√72)²] : [( √80)² -( √72)²]
=[(√80)² - 2*√80*√72 +(√72)²] : ( 80 - 72)]
=[ 8- 2*√16*√5*√36*√2 + 72 ] : 8
=[ 8 - 2*4*√5*4*√2 + 72 ] :8
=[ 80 - 32√10] :8
= 8(10 -4√10) :8
= 10 -4√10
2009-12-13T19:07:42+01:00
[√80 - √72]/[√80 +√72] - [√80 +√72]/[√80 -√72] =
=[4√5 -6√2]/[4√5 + 6√2] - [4√5 +6√2]/[4√5 -6√2] =
=[4√5 -6√2]²/[80 -72] - [4√5 + 6√2]²/[80 - 72] =
= [80 -48√10 +72]/8 - [80 + 48√10 +72]/8 =
= [80 -80 -48√10 -48√10 +72 -72]/8 = -96√10/8 = - 12√10